Co-creating value in organisations with ITIL 4 : a guide for consultants, executives and managers - Barrow, David (TSO, 2022)
Co-creating value in organizations with ITIL 4 explores how to achieve value across multiple business models using ITIL 4 at different stages of business and product evolution.